Effect of persistent pulmonary hypertension on brain oxygenation in asphyxiated term newborns treated with hypothermia. (2nd July 2016) - Gagnon, Marie-Helene; Wintermark, Pia
Abstract: Objective : To better understand the impact of persistent pulmonary hypertension (PPHN) on brain oxygenation in term asphyxiated newborns treated with hypothermia. Methods : The regional cerebral oxygenation saturation (rSO2 ) measured by near-infrared spectroscopy was compared to pre/post-ductal oxygen saturation and mean arterial blood pressure in three term asphyxiated newborns with documented PPHN during their first 4 days of life while they were being treated with hypothermia. Results : The cerebral oxygen saturation remained relatively stable when oxygen saturation was more than 92% and when there was no difference between pre- and post-ductal oxygen saturations. Episodes of desaturations with a difference between pre- and post-ductal saturations, as well as episodes of hypotension, caused a significant decrease in rSO2 in these newborns. Conclusion : This case series demonstrates that PPHN has a profound impact on brain oxygenation in term asphyxiated newborns treated with hypothermia during the first days of life after birth. PPHN may represent an additional risk factor for brain injury in these newborns during the first days of life.